Restorative Justice in Islamic Criminal Law: A Legal Psychology Perspective on the Necessity of Qisas and Diyat - M. Mujib Qulyubi; Muhammad Fadhlan Aziz; Adzanah Mariska Salsabila; Syahrul Anwar; Aris Hassama (International Journal of Nusantara Islam, 2026)
Restorative justice studies have so far been developed mainly within the framework of modern positive law, while the potential of similar concepts in Islamic criminal law is often narrowly understood as a mechanism of retribution. In fact, Qisas and diyat embody a more comprehensive dimension of justice-oriented towards restoration. The purpose of this study is to analyse Qisas and diyat in Islamic criminal law through the perspective of legal psychology to prove the restorative justice character inherent in them. This study uses a normative legal research method, with a conceptual, theological-normative, and legal psychology approach, examining primary data in the form of the Qur'an and hadith, as well as secondary data sourced from relevant research through library research, to analyse the restorative character of Qisas and diyat. The results of this study indicate that Qisas and diyat not only function as instruments of punishment but also as mechanisms of recovery that acknowledge victims' suffering, encourage perpetrators' moral responsibility, and restore social and psychological balance. The novelty of this study lies in the integration of a legal psychology perspective into the examination of Qisas and diyat as restorative justice inherent in Islamic criminal law. This research is expected to enrich academic discourse and strengthen the relevance of Islamic criminal law in the discourse of modern restorative justice.